PEMBERDAYAAN SPIRITUAL KORBAN PENYALAHGUNAAN NARKOBA DI PANTI REHABILITASI SOSIAL NARKOBA SAHABAT SUCI HATI KOTA PADANG - Rahmat Padli (UIN Imam Bonjol Padang, 2021)
Drug abuse committed by teenagers and adults can result in their future being threatened, it can harm religion, education, economy, health, can cause addiction to continuously consume drugs, and hinder the implementation of the worship of a religion. Therefore, it is necessary to have a solution in handling it so that teenagers and adults who are victims of drug abuse can recover from drug addiction. One of the solutions is that there is a need for spiritual empowerment carried out by people who are members of social drug rehabilitation centers in collaboration with the government, religious leaders, health experts and the National Narcotics Agency. the implementation of the spiritual empowerment of victims of abuse through the process of awareness, capacity and empowerment carried out by the management of the Narcotics Social Rehabilitation Institution, Sahabat Suci Hati, Padang City, has a positive influence. First, victims of drug abuse mostly recover from addiction to drug abuse, secondly, the increase in the quantity and quality of charities of worship for victims of drug abuse independently.